Potential of vegetable waste as alternative production bioelectricity - Yulviany Latuihamallo; Ferymon Mahulette; Theopilus Wilhelmus Watuguly (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2023)
Energy use is closely related to world economic growth and urbanization. Therefore, research was carried out by utilizing organic vegetable waste as a source of renewable energy. This study aims to determine variations in incubation time of vegetable waste that affect electricity production and to determine differences in bio-electricity production based on variations in incubation time of vegetable waste. The results of bioelectricity measurements in the Microbial Fuel Cell reactor, the maximum production of bioelectricity is found at the incubation period of 7 days, namely 9.48 mA at the 0th minute (initial), the maximum electric voltage is 288 mV at the 60th minute, the maximum power is 2205.50 mW in the 30th minute, and the maximum power density is 152.10 mW/m2 in the 30th minute.